A coupled structural and geotechnical assessment of the effects of a landslide on an ancient monastery in Central Italy. (15th December 2020) - Sangirardi, Marialuigia; Amorosi, Angelo; de Felice, Gianmarco
Highlights: An integrated approach of geometrical survey and safety assessment of cultural heritage is presented. Advanced laser-scanner survey is adopted for the geometrical reconstruction of the problem. Coupled geotechnical-structural numerical analyses are performed. Possible interaction between landslides and a masonry building is studied through FEM. Abstract: Every year landslides occur all over the world as a consequence of specific ground conditions, geomorphological, physical or man-made processes. Such phenomena, often triggered by heavy rainfalls or earthquakes, can affect buildings and infrastructures, causing economic and life losses. This work investigates the effects of a landslide, occurred on the 26th of November 2018, on the Monastry of Santa Scolastica in Subiaco (Rome), one of the most ancient and well-preserved examples of medieval architecture in Central Italy. The evolution of the damage pattern observed on the structure is discussed and related to its different causes, aiming at evaluating if possible worsening effects should or not be ascribed to the occurred landslide or to possible future similar events. The study relies on an accurate geometrical description of both the slope and the building, made possible by advanced survey tools. Most of the analyses used to simulate the history of the events occurred to the Monastry were performed by a three-dimensional non-linear finite element model. Elastic-perfectly plastic constitutive assumptions were adopted for the soil, while the structure was modelled by a three-dimensional anisotropic elastic-perfectly plastic constitutive model, specifically conceived for masonry, accounting for block dimensions and staggering joints effects. Finite element approach has proven to be very effective in the analysis of such a coupled interaction problem, leading to a realistic representation of the interplay between the soil displacements and their effects within the structure. The safety conditions of the structure could then be assessed, and the causes of the damage pattern identified, showing that the slope movement did not worsen the pre-existing damage conditions, which should instead be ascribed to the original soil-structure interaction phenomena occurred when an extension of the original structure had been built.